D4P4: A Neuro-Pedagogic Model for Developing High-Risk/ High-Precision Procedural Skills in Residency Training - Hermanto TJ (Asian Journal of Health Research, 2025)
Medical education stands at a pivotal juncture. The long-standing "see one, do one, teach one" model, once the cornerstone of clinical training, is increasingly inadequate for preparing today’s physicians. Rising resident-to-patient ratios, overwhelmed faculty, and the distinct learning preferences of Generation Z demand a more sophisticated and responsive approach. In response to these challenges, the D4P4 model emerges as a transformative framework—rooted in decades of neuroscience and educational theory—designed to cultivate high-risk, high-precision procedural skills in residency programs..